The devil in the details: The core disadvantage of the International Poverty Line - Michail Moatsos (ZBW – Leibniz Information Centre for Economics, 2020)
Our appreciation of global poverty almost exclusively relies on the official statistics published by the World Bank. Yet, these official global poverty estimates, based on the standard dollar-a-day approach, fall short in their prime objective of observing a constant standard of living across countries and over time. This paper discusses in brief the core methodological problem of the method, that is the idea that a single poverty line can be used for all country and all years consistently.
Keywords: I3; 330; Global Poverty; Absolute Poverty; Poverty Measurement; Dollar-A-Day; International Poverty Line; WBPL